2016
DOI: 10.1113/jp272231
|View full text |Cite
|
Sign up to set email alerts
|

Properties and dynamics of inhibitory synaptic communication within the CA3 microcircuits of pyramidal cells and interneurons expressing parvalbumin or cholecystokinin

Abstract: Key pointsr To understand how a network operates, its elements must be identified and characterized, and the interactions of the elements need to be studied in detail.r In the present study, we describe quantitatively the connectivity of two classes of inhibitory neurons in the hippocampal CA3 area (parvalbumin-positive and cholecystokinin-positive interneurons), a key region for the generation of behaviourally relevant synchronous activity patterns.r We describe how interactions among these inhibitory cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
95
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(112 citation statements)
references
References 75 publications
17
95
0
Order By: Relevance
“…However, there is strong evidence that an excitation/inhibition imbalance in presymptomatic animals contributes to the initial epilepsy predisposition (Boido et al, 2010;Fassio et al, 2011;Farisello et al, 2013;Feliciano et al, 2013). In the present study, we demonstrated that SynII deletion reduced IPSC amplitudes and prolonged the release kinetics in PV interneurons, which have a key role in the regulation of seizure propagation (Krook-Magnuson et al, 2013;Sessolo et al, 2015). Furthermore, extensive evidence links epilepsy with asynchronous activity of GABAergic synapses through tonic inhibition (Jiang et al, 2012;Pandit et al, 2013;Medrihan et al, 2015).…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…However, there is strong evidence that an excitation/inhibition imbalance in presymptomatic animals contributes to the initial epilepsy predisposition (Boido et al, 2010;Fassio et al, 2011;Farisello et al, 2013;Feliciano et al, 2013). In the present study, we demonstrated that SynII deletion reduced IPSC amplitudes and prolonged the release kinetics in PV interneurons, which have a key role in the regulation of seizure propagation (Krook-Magnuson et al, 2013;Sessolo et al, 2015). Furthermore, extensive evidence links epilepsy with asynchronous activity of GABAergic synapses through tonic inhibition (Jiang et al, 2012;Pandit et al, 2013;Medrihan et al, 2015).…”
Section: Discussionsupporting
confidence: 50%
“…The other parameters include the CA, the coefficient of variation (CV) of synaptic currents, the paired pulse ratio (PPR), and the failure rate (FR) of synaptic transmission (Neu et al, 2007;Daw et al, 2009;Bartos and Elgueta, 2012;Hu et al, 2014). A recent study demonstrated that cluster analysis can be used to classify these interneuron subtypes according to their intrinsic synaptic and spiking properties (Kohus et al, 2016). We conducted cluster analysis based upon five variables, including spiking (SF and CA) and synaptic (CV, FR, and PPR) parameters ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, CB1-positive basket cells receive large amount of subcortical inputs carrying information about the “inner world” of the brain [7] and modulate synchronous ensemble activity accordingly. Therefore, PV-positive basket cells are thought to function as “clockworks” for cortical network oscillations, whereas CB1-expressing interneurons operate as a “plastic fine-tuning device.” Perisomatic inhibition has an important role in the generation and regulation of sharp wave-ripples [8], gamma oscillations [9], and seizure-like activities [10] in rodent hippocampal slice preparations. The first attempts have been made to achieve seizure-control via manipulation of perisomatic inhibition in animal models, by selectively stimulate PV-positive neurons and by transplanting interneuron precursors [1113].…”
Section: Introductionmentioning
confidence: 99%